Coping strategy of porang farmer's household in anticipating long harvest period: Empirical study in Wonogiri Regency, Indonesia. Issue 1 (1st December 2022) - Irianto, H; Riptanti, E W; Mujiyo,
Abstract: Porang is one of the alternative foods commonly cultivated in several areas, including Wonogiri Regency, because this area is suitable for its development. The cultivation business is not devoid of challenges. The tubers of Porang experience a dormancy phase, resulting in a long growing period of 6 to 10 months. Therefore, this study aims to identify the coping strategies used by farmers to adapt the length of the porang harvest period. Furthermore, this study is qualitative in nature involving 180 farmers selected through a census. The snowball sampling method was used to select respondents from 6 sub-districts in Wonogiri Regency in Indonesia. Furthermore, the analysis was conducted descriptively using an index coping strategy for measurement. These results indicated that farmers employ 11 types of coping strategies. The application is performed by combining one type up with more than 4 others. Most of the coping strategies types are applied to 2 combinations, hence, its index is in a low category. The alternative is a realistic combination that farmers can choose based on human and other resource availability.